Hubungan Manajemen Pendidikan Inklusif terhadap Pembelajaran Anak Berkebutuhan Khusus (ABK) di SD Zion Palu: The Relationship between Inclusive Education Management and Learning for Children with Special Needs (ABK) at Zion Elementary School, Palu - Diana Gloria Estevania Palindu; Yusdin Bin. M. Gagaramusu; Dyah Rahmawati; Rizal Rizal; Nurlinda Nurlinda (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to determine the relationship between inclusive education management and the learning of children with special needs (ABK) at Zion Elementary School, Palu. This study uses a quantitative, correlational research design to test the relationship between inclusive education management variables (independent variables) and ABK learning (dependent variable). The population in this study comprised all teachers at Zion Elementary School in Palu, with a sample of 17 selected using a saturated sampling technique. Data collection was conducted using a questionnaire that had been tested for validity and reliability, making it suitable as a research instrument. Data analysis was carried out using descriptive and inferential statistics, including the Pearson Product-Moment correlation test, assisted by SPSS version 27. Before testing the hypothesis, a prerequisite normality test was conducted using the Shapiro-Wilk test. The results showed a correlation coefficient (r) of 0.407, indicating a moderate relationship. However, the significance test yielded a p-value of 0.105, which exceeds the significance level of 0.05, indicating that the relationship between the two variables was not statistically significant. These findings indicate that inclusive education management is related to the learning of children with special needs, but it is not a dominant factor directly influencing their learning. Therefore, improving the quality of learning for children with special needs requires support from other factors, such as teacher competence, the availability of infrastructure, and collaboration among relevant parties.